Assessment of the endocrine disrupting properties of bisphenol AF: a case study applying the European regulatory criteria and guidance - Laura Escrivá; Johanna Zilliacus; Ellen Hessel; Anna Beronius (BMC, 2021)
Abstract Background Scientific criteria to identify endocrine disruptors (ED) was recently implemented for plant protection products (PPP) and biocidal products (BP). A guidance document has been published by ECHA and EFSA in the context of ED criteria for PPPs and BPs. Methods In the present work, a case study was performed on Bisphenol AF (BPAF) to explore the application of the EU criteria and EFSA/ECHA guidance document for the ED assessment of a non-pesticide chemical regulated under REACH. A data dossier was built by a systematic literature search (Web of Science, Pubmed, Embase; n = 511), title/abstract screening (n = 124) and full text examination (n = 88). All the information was extracted and systematically reported for 309 parameters (100 for adversity; 209 for endocrine activity). The reliability of studies was assessed (SciRAP tool). Results Data were synthesized into 96 lines of evidence for adversity (n = 57), and endocrine activity (n = 39); and assessed by weight of evidence methodology. The initial analysis of the evidence indicated EATS-mediated adversity in mammals, therefore a mode of action (MoA) was postulated for both male and female adult exposure. Female MoA included estrogen receptor activation and altered steroidogenesis leading to ovarian dysfunction, altered estrous cycling and impaired female fertility. Male MoA was initiated by androgen receptor inhibition and altered steroidogenesis leading to dysfunction of male reproductive organs and impaired male fertility. Conclusions The overall conclusion of the ED assessment indicated that BPAF meets the ED criteria for human health. The steps described in the ED guidance document were successfully completed, resulting in a thorough, structured and transparent identification of BPAF as an ED. Advantages and limitations of applying the ED criteria and guidance for a REACH chemical are discussed.